The Inﬂuence of Physical Activity and Chess Sports on Children’s Physical Condition and Cognitive Functions - Ligita Šilinė; Tautvydė Danilčikaitė; Laura Žlibinaitė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Children who play chess improve their academic results, cognitive and social skills, however, both cognitive and physical abilities are important for healthy development. Recent evidence suggests that physical activity has a positive impact not only on children’s physical abilities but cognitive functions as well. Yet it is not clear the eﬀect of physical activity and chess on children’s physical condition and cognitive functions.